Immune-checkpoint inhibitors plus chemotherapy versus chemotherapy as first-line treatment for patients with extensive-stage small cell lung cancer - Caicun Zhou; Tao Jiang; Fei Zhou; Wencheng Zhao; Xiaomei Gong; Shengxiang Ren; Chunxia Su (Journal for ImmunoTherapy of Cancer)
We performed a meta-analysis to comprehensively investigate the efficacy and safety of immune-checkpoint inhibitors (ICIs) plus chemotherapy in patients with extensive-stage small cell lung cancer (ES-SCLC). The primary outcome was overall survival (OS). The secondary outcomes included progression-free survival (PFS), objective response rate (ORR) and ≥grade 3 adverse events (AEs). A total of six studies involving 2905 patients were identified, including 469 patients receiving program death ligand 1 (PD-L1) inhibitor plus chemotherapy, 308 receiving PD-1 inhibitors plus chemotherapy, 563 receiving CTLA-4 inhibitors plus chemotherapy, 268 receiving PD-L1/CTLA-4 inhibitors plus chemotherapy, and 1297 receiving chemotherapy alone. 10.8% (283/2615) patients had baseline brain metastases (BMs). Notably, ICIs plus chemotherapy was associated with significantly improved OS (HR, 0.82; 95% CI, 0.75 to 0.89). Subgroup analyses revealed that PD-1 inhibitors (HR, 0.77; 95% CI, 0.64 to 0.92) and PD-L1 inhibitors (HR, 0.73; 95% CI, 0.63 to 0.85) plus chemotherapy yielded a statistically significant improvement in OS while CTLA-4 inhibitors did not (HR, 0.92; 95% CI, 0.81 to 1.06). In patients with baseline BMs, ICIs plus chemotherapy showed no survival benefits over chemotherapy alone (HR, 1.23; 95% CI, 0.92 to 1.64). ICIs plus chemotherapy also significantly prolonged PFS (HR, 0.81; 95% CI, 0.75 to 0.87) while the pooled ORRs were comparable between ICIs plus chemotherapy and chemotherapy alone (RR, 1.04; 95% CI, 0.99 to 1.10). Patients treated with CTLA-4 inhibitors (relative risk (RR), 1.12; 95% CI, 0.99 to 1.28) experienced more≥grade 3 AEs than those treated with PD-1/PD-L1 inhibitors (RR, 1.03; 95% CI, 0.96 to 1.11). The addition of PD-1/PD-L1 inhibitors to chemotherapy resulted in significant improvements in both PFS and OS for patients with treatment-naïve ES-SCLC, not at the cost of increased AEs.